Developing a procedural framework for advanced debtor protection : the case of emolument attachment orders - Van der Merwe, Stephan (Stellenbosch : Stellenbosch University, 2022)
Van der Merwe, S. 2022. Developing a procedural framework for advanced debtor protection : the case of emolument attachment orders. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/39ad8581-1ba5-4c45-8577-3dd8bd737415